HADITH, IDEOLOGY, AND DIGITAL AUTHORITY: A Van Dijk Critical Discourse Analysis of @hadits_lemah’s Instagram Posts - Aisyah, Aisyah; Najib, Abdul; Nawwaf, Aufa Varrassyah; Mubarok, Abdullah (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2026)
This study examines how discourses surrounding hadiths of fadail al-a’mal fadail al-a’mal are employed as propagative material on the Instagram account @hadits_lemah using Van Dijk’s critical discourse analysis. The account utilizes hadiths to disseminate particular Islamic teachings and ideological perspectives through social media. Employing a netnographic approach, this study investigates how hadith-based content functions in constructing and transmitting Islamic discourse in digital spaces. The findings reveal three main points. First, the nine posts analyzed display a similar textual pattern in which the main discourse is communicated visually through images, supplemented by captions and illustrations. Second, the content shapes social cognition by promoting concerns over practices considered heretical and polytheistic, which are associated with the widespread circulation of weak and fabricated hadiths accompanied by biased evaluations of their authenticity. Third, the emergence and growth of @hadits_lemah are closely linked to Indonesians’ increasing reliance on digital media and the transformation of social media into a contested arena for disseminating Islamic ideologies. Through its criticism of perceived deviant practices, the account seeks to maintain the relevance of its ideological position. This study contributes to the development of Van Dijk’s discourse analysis in the context of social media by emphasizing visual characteristics alongside semantic structures. It also highlights the importance of digital literacy in responding to ideologically driven religious content circulating online.Penelitian ini mengkaji bagaimana wacana hadis-hadis fadail al-a’mal dimanfaatkan sebagai materi dakwah pada akun Instagram @hadits_lemah dengan menggunakan analisis wacana kritis Van Dijk. Akun tersebut memanfaatkan hadis untuk menyebarkan ajaran dan perspektif keislaman tertentu melalui media sosial. Dengan menggunakan pendekatan netnografi, penelitian ini menelaah bagaimana konten berbasis hadis berfungsi dalam membangun dan mentransmisikan wacana keislaman di ruang digital. Hasil penelitian menunjukkan tiga temuan utama. Pertama, sembilan unggahan yang dianalisis memiliki pola tekstual yang serupa, di mana wacana utama disampaikan secara visual melalui gambar yang dilengkapi dengan keterangan (caption) dan ilustrasi pendukung. Kedua, konten yang disajikan membentuk kognisi sosial dengan menumbuhkan kekhawatiran terhadap praktik-praktik yang dianggap bid‘ah dan syirik, yang dikaitkan dengan maraknya penyebaran hadis lemah dan palsu disertai penilaian kualitas hadis yang bias. Ketiga, kemunculan dan perkembangan akun @hadits_lemah berkaitan erat dengan meningkatnya ketergantungan masyarakat Indonesia terhadap media digital serta menjadikan media sosial sebagai arena kontestasi penyebaran ideologi Islam. Melalui kritik terhadap praktik yang dipandang menyimpang, akun tersebut berupaya mempertahankan relevansi posisi ideologisnya. Penelitian ini berkontribusi pada pengembangan analisis wacana Van Dijk dalam konteks media sosial dengan menekankan karakteristik visual di samping struktur semantik. Selain itu, penelitian ini menegaskan pentingnya literasi digital dalam menyikapi konten keagamaan yang sarat dengan muatan ideologis di ruang digital.